Corporal Punishment in Educational Context: Criminal Law Regulatory Framework - Godeliva Ayudyana Suyudi; Fanny Tanuwijaya; I Gede Widhiana Suarda; Glenn Wijaya (University of Jember, Indonesia, 2023)
Teachers may impose sanctions or Corporal Punishment on students for educational purposes. In several cases, the Corporal Punishment action taken by the teacher resulted in the imposition of criminal sanctions on the teacher. This paper describes the perspective of criminal law settlement in Corporal Punishment cases. This paper uses the normative juridical research method, which examines the application of positive legal norms. Hence, this paper interprets the corresponding law in the means of textually. Furthermore, researchers use a conceptual framework to illustrate a teacher’s professional duties and Corporal Punishment. Finally, this research uses qualitative descriptive analysis supported by a case approach. This research found that applying life skill-based and contextual learning methods may prevent the aftermath of teachers’ Corporal Punishment. Teachers, carrying out their professional duties, may avoid criminal charges for Corporal Punishment if these actions do not exceed reasonable limits, which result in student losses, both physically and psychologically. The functionalization of criminal law may be prevented using ultimum remedium in resolving Corporal Punishment cases. This may occur in settlement through restorative justice, which involves various parties in the educational process. Alternatively, criminal law settlement may be used in Corporal Punishment cases. Judges may apply the concept of individualized punishment in imposing sanctions on teachers who are proven guilty of Corporal Punishment. Finally, this paper recommends a psychological intervention to assess educators’ mental capacity. This may take form through periodic assessments to determine the competence of teachers as educators.